2013
DOI: 10.5588/ijtld.12.0697
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of treatment for latent tuberculosis infection: prospective cohort study in the United States and Canada

Abstract: This is the first prospective multisite study to examine predictors of LTBI treatment acceptance in general clinic populations. Greater efforts should be made to increase acceptance among health care workers, those previously recommended for treatment and those who expect problems with LTBI medicines. Ensuring convenient clinic schedules and TB education to increase knowledge could be important for ensuring acceptance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 0 publications
1
39
5
Order By: Relevance
“…Each of the 12 TBESC sites was associated with one to five public health clinics that enrolled study participants; enrollment into the larger study is discussed in Colson et al 10 This analysis follows the 1515 enrollees who accepted LTBI treatment (see Colson et al for an analysis of LTBI treatment acceptance 10 ); of this group, the clinic charts of 192 participants could not be located, resulting in 1323 participants with evaluable outcomes and therefore eligible for the completion analysis. The 192 participants lacking chart information were concentrated in two clinics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each of the 12 TBESC sites was associated with one to five public health clinics that enrolled study participants; enrollment into the larger study is discussed in Colson et al 10 This analysis follows the 1515 enrollees who accepted LTBI treatment (see Colson et al for an analysis of LTBI treatment acceptance 10 ); of this group, the clinic charts of 192 participants could not be located, resulting in 1323 participants with evaluable outcomes and therefore eligible for the completion analysis. The 192 participants lacking chart information were concentrated in two clinics.…”
Section: Resultsmentioning
confidence: 99%
“…See Colson et al 10 and Pettit et al 11 for further details on in-person interviews and chart abstraction. At each site, the study coordinator and clinic director determined who would complete the clinic survey, in which information was collected on clinic population, procedures, and services.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[73][74][75][76] By focusing on screening high-risk population groups for TB reactivation, individuals may be identified and educated about LTBIs and recommended treatment. 77 Together with cost-effective diagnostic measures, educa- Tuberculin skin tests are preferred over interferon-␥ release assays as the diagnostic tool in children Ͻ5 years old.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that among healthcare workers, 52% rejected treatment [4]. Another American study also showed poor uptake of treatment for LTBI among healthcare workers, possibly suggesting that they might have some doubts about whether treatment of LTBI is beneficial to them personally [5].…”
Section: Introductionmentioning
confidence: 98%